The boss eaudiobook - Barnette, Abigail (Boss, 2015)
Sophie Scaife almost ran away once, trading her ticket to college for a ticket to Tokyo. But a delayed flight and a hot one-night stand with a stranger changed her mind, putting her firmly on track to a coveted position at a New York fashion magazine. When the irresistible stranger from that one incredible night turns out to be her new boss—billionaire and publishing magnate Neil Elwood—Sophie can't resist the chance to rekindle the spark between them . . . and the opportunity to explore her submissive side with the most dominant man she's ever known. Neil is the only man who has ever understood Sophie's need to submit in the bedroom, and the only man who has ever satisfied those desires. When their scorching, no-strings-attached sexual relationship becomes something more, Sophie must choose between her career and heart . . . or risk losing them both.